INVESTIGATION OF ADDITIVELY MANUFACTURED ALSI12 KELVIN LATTICE STRUCTURES - Raimbekov, Olzhas (Nazarbayev University School of Engineering and Digital Sciences, Department of Mechanical & Aerospace Engineering, 2024)
Additive Manufacturing (AM) has facilitated the production of parts with complex geometries. A particularly notable application of AM lies in the development of structured materials or lattice structures, where the mechanical attributes are dictated more by shape and design than by the material's microstructure itself. Lattice structures are crafted by designing the unit cell's topology in every direction of space. This in turn offers lightweight and customizable mechanical characteristics for applications in aerospace, biomedical, and automotive fields. Although research has been conducted on lattice structures made from materials such as Ti, AlSi12Mg, and Fe alloys, studies on lattices composed of AlSi12 alloys are somewhat limited. However, given their lower density compared to steel, AlSi12 alloys represent a potentially more economical alternative to Ti-based alloys. Despite this advantage, the production of lattice structures from AlSi12 alloys has not become widespread. This study is devoted to the mechanical properties of compression of lattice structures of AlSi12 alloy. It describes how these properties and energy absorption capabilities are affected by structure geometry, evaluates the impact of different thermal treatments on performance, and explores new lattice configurations with improved performance by combining Kelvin lattice and BCC lattice. A study was carried out on kelvin lattices with different strut diameters and unit cell sizes to evaluate their mechanical properties and energy absorption capacity. It has been found that non heat treated lattices have a significantly higher energy absorption capacity than those that have been heat treated. Among them, the as-built kelvin lattice combined with the BCC configuration showed the maximum energy absorption capacity measured at 416 MJ/m^3. In contrast, a heat-treated kelvin lattice with a unit cell size of 6 mm demonstrated a minimum capacitance of 9 MJ/m^3. The as-built lattice exhibits superior mechanical characteristics but demonstrates considerable brittleness. This results in the formation of a shear band during compression, leading to a separative failure of lattice. This problem is directly related to the microstructural composition of the alloy, which includes a fibrous network of silicon surrounding a delicate Al phase. In addition, it has been observed that heat treatment negatively affects the energy absorption ability of the lattices. The effect of heat treatment varies depending on various mechanical aspects such as yield stress, Young's modulus and plateau stress. Notably, heat treatment changes the stress-strain behavior from a stretch dominated response to a bending dominated response. Through microstructural research, it was observed that heat treatment leads to the formation of Si agglomerates, which increase the ductility of the lattices.
Keywords: Additive Manufacturing; AlSi12; SLM; Kelvin Lattice; Lattice Structures; type of access: open access